Miscible Water Alternating Gas CO2 Injection Performance Analysis as Efforts to Improve Oil Recovery Factors in Field CW - Citra Wahyuningrum; Muhammad Taufiq Fathaddin; Asri Nugrahanti; Esaim Mustafa Abrahim Omar (Journal of Earth Energy Science, Engineering, and Technology, 2022)
The Enhanced Oil Recovery (EOR) method aims to increase oil production. One of the EOR methods is CO2 injection. CO2 injection mechanism is by expanding the volume of oil, reducing viscosity, and reducing the mobility ratio. The purpose of the study was to compare the recovery factor gain in the waterflood, Miscible CO2 Continuous injection, and Miscible WAG CO2 injection methods with a three-dimensional simulation methodology using CMG Compositional software in the CW Field. From the CW field, a sectoral model was chosen to be studied, namely the area of the CW-A well and the CW-B well because the two areas have different reservoir conditions. The optimal injection well pattern for the CW-A Well area and the CW-B Well area is Inverted Five Spot. CO2 injection is said to be miscible because the injection pressure and reservoir pressure are above MMP (2800 psi) and mixing occurs between CO2 and oil to form a homogeneous phase. The optimal CW-A (Low Permeability) well area using the 4 PV CO2 Continues Injection scenario (injection rate 31.8 Mscf/d) produces an RF of 61.18%. Optimal CW-B (High Permeability) Well Area using CO2-WAG 2 PV injection scenario in 90 days (3 months) cycle, WAG Ratio 1:3 (injection water rate 20,036.84 bwpd and gas injection rate 33.75 Mscf/d) produces RF of 61.76%.